Factors Influencing the Efficiency of Commercial Banks in Nepal - Shrestha, Swechchha Jyoti (Apex Journal of Business and Management, 2025)
This study examines the factors influencing the efficiency of commercial banks in Nepal. The research focuses on how selected financial indicators relate to overall bank efficiency, using the DEA-CCR model for measurement. The analysis draws on panel data from 20 commercial banks in Nepal over a period of seven years, resulting in 140 observations. The study employs descriptive statistics, stationarity tests, and panel regression analysis to assess the relationship between the dependent variable (efficiency) and five independent variables: cost to income ratio, capital adequacy ratio, asset size, asset quality, and non-performing loan ratio. The results reveal that asset size and asset quality have a statistically significant positive impact on efficiency, suggesting that larger banks with higher-quality assets are more efficient in utilizing their resources. On the other hand, the non-performing loan ratio has a statistically significant negative effect on efficiency, indicating that rising default levels erode operational performance. Both the cost to income ratio and capital adequacy ratio show no significant relationship to efficiency, implying that these factors may not directly influence productivity in Nepalese commercial banks. These findings highlight the need for banks to grow responsibly, focus on maintaining high-quality assets, and take proactive steps to reduce default risk. For bank managers, regulators, and policymakers, this study offers useful insights into what really drives efficiency and where efforts can be best directed to strengthen the overall banking sector in Nepal.